2021
DOI: 10.1007/s40121-021-00457-z
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Glycoprotein Polymorphisms and Increasing Viral Load in Non-Transplant Patients with Hematological Malignancies Undergoing Chemotherapy: A Prospective Observational Study

Abstract: Introduction: Cytomegalovirus (CMV) predisposes to several clinical complications and is a major cause of morbidity and mortality in immunocompromised patients, including patients with hematological malignancies (HM). The present study was carried out to determine the distribution of CMV glycoprotein B, N, and O (gB, gN, and gO) genotypes and their potential effect on its viral load and on clinical outcomes in a cohort of Tunisian nonhematopoietic stem cell transplant (HSCT) patients with HM undergoing chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
(124 reference statements)
0
1
0
Order By: Relevance
“…A previous study has shown that the mixed gN genotype is associated with a greater risk of severe lymphopenia and increased risk of death than single gN genotype infection. 26 Another study showed that mixed gN genotype infections were not associated with the presence or absence of clinical phenotypes and sensorineural hearing loss, but that study had a small number of symptomatic children, while the relevance of hepatitis as a clinical phenotype to mixed gN genotype infection has not been explored separately. 27 Although the mechanisms by which mixed genotype infections increase the development of hepatitis need to be further explored in this study, the results suggest that patients with active HCMV infection who have detectable mixed gN genotype infections should be monitored closely for the possibility of developing hepatitis, and early targeted interventions should be implemented to reduce the impairment of liver function.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has shown that the mixed gN genotype is associated with a greater risk of severe lymphopenia and increased risk of death than single gN genotype infection. 26 Another study showed that mixed gN genotype infections were not associated with the presence or absence of clinical phenotypes and sensorineural hearing loss, but that study had a small number of symptomatic children, while the relevance of hepatitis as a clinical phenotype to mixed gN genotype infection has not been explored separately. 27 Although the mechanisms by which mixed genotype infections increase the development of hepatitis need to be further explored in this study, the results suggest that patients with active HCMV infection who have detectable mixed gN genotype infections should be monitored closely for the possibility of developing hepatitis, and early targeted interventions should be implemented to reduce the impairment of liver function.…”
Section: Discussionmentioning
confidence: 99%